Imobilisasi Enzim Lipase Dedak Padi (Oryza Sativa L.) Pada Karbon Aktif: Karakterisasi, dan Uji Stabilitas Kerja Enzim Imobil - Firdaus, Firdaus; Dali, Seniwati; Rusman, Hendra J. (Indonesian Journal of Chemical Research, 2017)
This research aims to immobilization; characterize the enzyme of immobilized, test the effectiveness of the enzyme of immobilized. This research begins with the immobilization to process of enzyme lipase using activated carbon matrix, enzyme characterization covering of immobile determination of temperature and pH optimum of the enzyme of immobilized, as well as test the stability of work covering immobilized of enzyme the test thermal stability and repeated use. The results showed that the immobile of enzyme work optimally at 50oC of temperature and pH 6.5 with each activity 0.040 U/mL; research results also showed that the immobile of enzyme has higher thermal stability in comparison with the free enzyme: with the relative activity of 57.50% at the time of 45 minutes of exposure and the exposure time at 47.50% at 75-105 minutes and it can be used as many as six times with the relative activity of 52.5% in 6 times of use.